Nuclear bodies: Built to boost - Sawyer, Iain A. (J Cell Biol, 2016)
The classic archetypal function of nuclear bodies is to accelerate specific reactions within their crowded space. In this issue, Tatomer et al. (2016. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201504043) provide the first direct evidence that the histone locus body acts to concentrate key factors required for the proper processing of histone pre-mRNAs.